Study habits and technology use in Italian university students - Andrea Poscia; Emanuela Maria Frisicale; Paolo Parente; Daniele Ignazio La Milia; Chiara de Waure; Maria Luisa Di Pietro (Istituto Superiore di Sanità, 2015)
BACKGROUND: Students' ability of learning is influenced by study habits. Among these, the use of technologies has assumed a controversial role. The aim of this paper is to analyse studying approach, the use of technologies and how they affect study habits in a population of university students addressed by the "Sportello Salute Giovani" ("Youth Health Information Desk") questionnaire. METHODS: 16 questions referred to the approach to studying and the use of technologies (number 77-93) were analyzed. Absolute and relative frequencies were calculated. Stratification for sex, age and socio-economic status were performed and Chi square test was used to test the difference between sex, age class and socio-economic groups. RESULTS: 99.7% of students declared to have at least one mobile phone and 68.7% to use smartphones, i-phones and i-pads. Males (20.9% vs 14.9% female, p < 0.05), older students (31.7% among 25-30 years old students vs 21.3% among 18-21 years old, p < 0.05) and students with the highest socio-economic level (87.8% vs 54.2% of the lowest) seem more likely to use digital technologies/Internet for educational purposes. CONCLUSION: Our survey revealed that most college students still prefer approach the study using books instead of digital tools, but this attitude is conflicting with how many hours they use computers and surf Internet per weeks. Therefore, further studies are needed to understand better technology influence on study habits and its implication on health.